Identificação de genótipos de feijão-caupi para produção de biomassa de forragem - Barroso Neto, Antônio Moreira (2021)
In the search for new legumes species to compose the forage mix, the CAUPI beans [Vigna Unguiculata (L.) Walp.] It has been a little studied in Brazil for such purpose, despite several studies in the world that prove the potential of this species for forage production. The objective was to elaborate a selective index that allows to aid in the recommendation of CAUPI bean cultivars for forage production and to select the best genotypes based on it. The essay was conducted on the Experimental Farm Vale do Curú (FEVEC / UFC), located in the municipality of Pentecote-CE. 64 genotypes were evaluated, 61 are accessed from the Germlasm Bank of the Federal University of Ceará, and 3 genotypes from Embrapa Climate Temperado-RS, which are cultivated for forage production. The experimental design used was simple latica (8x8), with two replicates. Each treatment was represented by a portion consisting of five lines of 4 m in length and spaced at 0.50 m, presenting as useful area the three central rows. The physiological and morphological characteristics were evaluated. Devian's analysis revealed significant differences in the effects of genotype for most characters. It was significant for initial fluorescence genotypes (Fo), coefficient of photochemistry (qP), non-photochemical dissipation coefficient (qN), relative chlorophyll index (IRC), canopy height (AD) and leaf area index (IAF). This indicates differences in the relative responses of genotypes for evaluated characters. There was a correlation between the morphological characteristics (AD and IAF) and physiological (Fo, IRC, qN, qP), of Caupi beans. Three different disposal (Fo, qN, IAF) variables were identified. Based on the communality, the signs and magnitudes of the initial and final factorial charges, three character groups were identified. For each group, the correlations between the characters were moderate magnitude, therefore, it was possible to discard the characters that were relatively difficult to measure and / or were redundant in each group, such as FO in Group 2 and IAF in Group 3. Generally, a selection index was obtained I2 = 0.066169 IRC + 0,191538 qP + 0.661189 AD. This index allows you to recommend promising bean-cuupi genotypes for forage production.